Analisa Faktor terhadap Kejadian Anemia Ibu Hamil Trimester III di Puskesmas Sangiang Kota Tangerang Tahun 2022 - Siti Maesaroh; Nur Anita (Jurnal Keperawatan Muhammadiyah, 2023)
Background: Anemia of pregnancy in pregnant women is characterized by Hb levels lower than 11 g%. Anemia of pregnancy is often a "potential danger to mother and child." Anemia conditions increase the risk of sepsis, bleeding and even death in the mother, prematurity, perinatal death, and low birth weight. From some of the literature it is stated that the factors for the occurrence of anemia in pregnant women consist of the mother's age, parity, level of knowledge, and behavior or adherence to consuming iron/Fe tablets.Objective: To identify and analyze the factors that are related or dominantly influence the incidence of anemia in third trimester pregnant women at the Sangiang Community Health Center, Tangerang City in 2022.Methods: This research includes analytic observational design with case control population data and samples using secondary medical record data from October-November 2022. The subjects of this study were 36 third trimester pregnant women as samples and were taken using a purposive random sampling technique. Analysis of univariate bivariate and multivariate data using the frequency distribution, bivariate with chi-square test followed by a regression test for multivariate analysis.Result: The results showed that the characteristics of third trimester pregnant women were more in pregnant women with age not at risk (63.9%), parity not at risk (55.6%), high school/vocational school education level (33.3%), working (55.6%). The factor that is significantly related to anemia in pregnant women is the behavior of third trimester pregnant women in consuming Fe tablets (p-value: 0.005; OR: 0.600). Factors that were not related to anemia were mother's knowledge (p-value: 0.613 OR 1.875), parity (p-value: 0.191 OR 1.760), mother's age (p-value: 0.301, OR 1.800).Conclusions: The risk factors that jointly influence the incidence of anemia in third trimester pregnant women are mother's knowledge, parity, and age of mother. The factors that have the greatest influence on the incidence of anemia are compliance/behavior of pregnant women in consuming Fe tablets, then knowledge of the mother, parity, and age of the mother